An enquiry into the production of peripheral neuritis by pressure due to action or posture - MacKay, William Robert Hope (The University of Edinburgh, 1937)
I. The normal function of peripheral nerves is frequently interrupted by pressure, produced by some action or posture of the patient. II. The condition usually passes off rapidly, and it is only the more persistent types, which come to the notice of the practitioner. III. The longer and more exposed peripheral nerves are those most commonly affected. It is also to be noted that the nerves, compression of which causes little pain, are those most frequently affected by pressure neuritis, due no doubt to pain reaching consciousness, as a warning signal, sooner than paraesthesia. IV. The patient seldom connects his action or posture and his neuritic manifestations as cause and effect. V. Establishment of the diagnosis as well as the treatment depends upon the discovery of the action or posture responsible. To achieve this great care must be exercised in taking the history, with possibly occasional resort to leading questions. VI. The condition appears more frequently in thin than in fat subjects, and in men more often than in women. Cold and damp appear to play a part in increasing the incidence of the condition. VII. The pathological changes,occurring in the nerve,depend upon the severity and duration of the compression. They range from temporary ischaemia and a localized area of degeneration, with or without solution of continuity of the axon,to intraneural fibrosis and complete nerve destruction. VIII. A favourable diagnosis can usually be given, spontaneous recovery occurring in every case once the cause has been recognised and its recurrence obviated. IX. Treatment, apart from the safeguarding of the nerve against further injury, is directed chiefly towards maintaining the tone and nutrition of the structures, which have been temporarily deprived of their nerve supply.